Pengembangan LKPD Pembelajaran Matematika Berbasis Etnomatematika Pasar Satelit Lubuklinggau pada Materi Aritmatika Sosial - Jaya, Patlan Putra; Elly, As; Fitriyana, Nur (Program Studi Pendidikan Matematika, 2024)
This research aims to produce ethnomathematics-based LKPD for the Lubuklinggau satellite market on social arithmetic material for class VII MTs that is valid, practical and effective. To determine the validity of this research, a validation test was carried out from material, media and language experts, while to determine the practicality of this research, it was seen from the results of the teacher and student (small group) practicality questionnaire, and to determine the effectiveness of this research, it was seen from the results of the field test ( field test). This research is development research using the ADDIE development model, which consists of stages: Analyze, Design, Development, Implementation, and eval_____uation. Data collection techniques were through interviews, observations, questionnaires and tests, with the research subjects being class VII students at MTs Negeri 1 Lubuklinggau, totaling 6 people for the small group test and 17 students for the field test. Based on the results of data analysis, it shows that the Aiken's V value from material expert validation is 0.82, media expert is 0.92 and language expert is 0.90 with a very valid category. In the practicality test, teachers and students obtained an overall percentage of 86.5% in the very practical category. And the results of the effectiveness test through tests given by 17 students obtained an average score of 0.71 using the N-Gain formula and is included in the criteria for high or very effective use in the learning process